Optically transparent magnetic nanocomposites based on encapsulated Fe3O4 nanoparticles in a sol-gel silica network - Thomas, Senoy; Sakthikumar, D.; Joy, Pattayil Alias; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanotechnology, 2006)
Composite Fe3O4-SiO2 materials were prepared by the sol-gel method with tetraethoxysilane and aqueous-based Fe3O4 ferrofluids as precursors. The monoliths obtained were crack free and showed both optical and magnetic properties. The structural properties were determined by infrared spectroscopy, x-ray diffractometry and transmission electron microscopy. Fe3O4 particles of 20 nm size lie within the pores of the matrix without any strong Si-O-Fe bonding. The well established silica network provides effective confinement to these nanoparticles. The composites were transparent in the 600-800 nm regime and the field dependent magnetization curves suggest that the composite exhibits superparamagnetic characteristics.